7.5: Research on Quantum Dots and Phosphor Blend Backlight Module. (4th October 2019) - Li, Hao; Li, Fulin; Qiao, Mingsheng; Mu, Linjia; Zhang, Dengyin
Abstract : In order to improve the light efficiency and color gamut of the quantum dot backlight module, a high efficiency and high color gamut backlight module is designed. The green quantum dots are prepared into a green light conversion film, and red KSF powder is added to the package of the blue LED. The red KSF powder exhibits better narrow spectral characteristics and heat resistance than the red quantum dots, and the narrow spectral characteristics can enhance the backlight gamut range and make the LCD display more colorful. And since the red KSF powder is encapsulated in the blue LED, it does not absorb the green light converted by the green quantum dot film, thereby improving the luminous efficiency and improving the display brightness. At the same time, in order to overcome the chromatic aberration between the center of the screen and the screen, the difficulty of the purple around the screen, a phosphor dot light guide plate was designed, and the light guide plate dot at the edge of the screen was replaced with a green phosphor dot to complement the purple backlight. Thereby achieving a uniform color throughout the screen.